Investigating the Impact of Social Media Marketing Activities on Customer Satisfaction with the Mediating Role of Brand Equity and Perceived Value - Seyed Masoud Mirbabaei1; Bahareh Ahmadinejad; Maryam Hajmalek; Mohsen Shojaeifard; Elias Laalkazemian (Asian Journal of Business and Accounting, 2023)
Manuscript type: Research paper Research aims: In today’s businesses, social networks are seen as an applicable instrument for influencing consumer behaviour, raising awareness, connecting with consumers, and improving service quality and satisfaction. The present study analyses the effectiveness of social media marketing activities to expand the use of XX insurance online services and it investigates how social marketing initiatives affected consumers’ satisfaction using brand awareness and perceived value as mediating factors. Design/Methodology/Approach: This research used an experimental study, using a survey method (questionnaire distribution), to confirm the hypotheses and discover its management concepts, and uses Structural Equation Modeling (SEM). Research findings: The results showed that the social media marketing activities variable (entertainment, interaction, trendiness, customisation, perceived risk) has a positive and significant impact on customer satisfaction, with brand image, brand awareness, perceived value, and social identity serving as mediating factors. Social identity has an influence on perceived value as well as social marketing initiatives do have on consumer satisfaction.